Increasing Productivity of “Kerupuk Puli Bu Iis” in Tambakmas, Sukomoro, Magetan - Ruhana, Amalia; Tri Rahayu, Imami Arum; Saksono, Lutfi (Center for Community Service and Science and Technology Marketing - The Institute for Research and Community Service Universitas Negeri Surabaya, 2023)
Abstract “Kerupuk Puli” or commonly referred to as “LEMPENG” are one type of cracker originating from the residency of Madiun. These crackers come from rice and use garlic as a flavoring. The savory taste and crunchy texture make the number of people who consume these crackers increase. In bu Iis’ business, the most conspicuous problem is in the cutting process. Cutting this dough is a production stage that requires precision, accuracy, and hygiene. Bu Iis' business still uses manual or human hands and a knife to cut so that the speed and accuracy of the size and cleanliness when cutting the cracker dough is not guaranteed. To overcome this problem, Bu Iis' business must get a touch of appropriate technology in the form of a cracker dough cutting machine. The cracker cutter is done manually, in 1 minute only about 10 slices of crackers are produced. But when done using a cracker cutting machine, it can produce 30 pieces of crackers per minute. With the help of this tool, the production process for cutting cracker dough can be done faster, so as to increase the production capacity of crackers.